Effects of Breed and Storage Duration on the Beta-Carotene Content of Egg Yolk - Okonkwo, J.C. (Pakistan Journal of Nutrition, 2009)
Effects of breed (Harco, White Leghorn and Local breeds) and storage durations (point of lay, 1-week, 2-week and 3-week) on the beta (ß)-carotene contents of egg yolk were studied using one hundred and twenty eggs for each breed. The ß-carotene contents of the egg yolks were determined using spectrophotometer and data obtained were analyzed using ANOVA and differences between means were separated using DNMRT. The mean concentration in mg/g of ß-carotene obtained for each breed and at different storage durations were: 0.08 (Harco), 0.06 (White Leghorn) and 0.06 (local breed) at point of lay; 0.031 (Harco), 0.047 (White Leghorn) and 0.54 (Local breed) for 1-week old eggs; 0.014 (Harco), 0.027 (White Leghorn) and 0.039 (Local breed) at two weeks and 0.000 ( Harco), 0.004 (White Leghorn) and 0.024 (Local breed) at three weeks of age. Generally, the results revealed that eggs from Harco breed had the highest and most unstable concentration of ß-carotenes, while the eggs from the local breed had the greatest propensity to retain ß-carotene. Consequently, eggs are best consumed at the point of lay or as soon as possible especially eggs from Harco breed if the ß-carotene content is desired. Furthermore, eggs from local chickens may be stored for a longer period without remarkable decrease in ß-carotene content of the egg yolk. The study further recommends to researchers and poultry breeders who are interested in improving the beta-carotene content as well as the storage duration of eggs to consider seriously crossing of black harco breed with local breed.